Identificação e priorização dos fatores críticos de sucesso na implantação de fábrica digital - de Carli, Paulo Cesar [UNESP]; Delamaro, Mauricio Cesar [UNESP]; Salomon, Valério Antonio Pamplona [UNESP] (FapUNIFESP (SciELO), 2010)
A Digital Factory is a concept which improves the collaboration among product development processes. Despite the benefits brought by this concept, failures may occur in its implementation. This paper aims to present the Critical Success Factors in the implementation of a Digital Factory project in a Brazilian company. These factors were identified by an exploratory survey on the implementation of Enterprise Resource Planning and Product Lifecycle Management among other systems. Following this identification, the factors were prioritized using the Delphi Method and the Analytic Hierarchy Process; this evaluation was carried out by professionals from enterprises which implement Digital Factory projects, in Brazil and abroad. Nine factors were identified. The five main priorities were: Continuous Support and Commitment from Top Management; Comprehensive Business Reengineering; Skilled and Experienced Partners; Participation and Commitment of Users; and Appropriate Role of the Project Manager.
Identification and prioritization of critical success factors in a digital factory implementation
Keywords: AHP; Critical success factors; Delphi method; Digital factory